Implementation of the Independent Learning Curriculum in Islamic Religious Education Subjects Based on Humanistic Theory at Senior High School - Nadhuha, Nadhuha; Murniati, Andi; Tohirin, Tohirin (STIT Ahlussunnah Bukittinggi, 2025)
This study aims to analyze the implementation of the Independent Learning Curriculum in Islamic Religious Education subjects at SMK Akbar Pekanbaru based on Humanistic theory. The Independent Learning Curriculum emphasizes flexible learning, based on students' needs and potential, and provides space for students to explore learning independently. Humanistic theory emphasizes self-development, self-actualization, and the importance of positive relationships between teachers and students. This study used qualitative methods with data collection techniques in the form of interviews, observation, and documentation. The results of the study indicate that the implementation of the Independent Learning Curriculum at SMK Akbar Pekanbaru in Islamic Religious Education subjects based on humanistic theory is implemented through: 1) learning that is fun, free, non-monotonous and emphasizes student activity through the development of cognitive, affective and psychomotor aspects, and teachers use cooperative learning models,direct instruction, and small discussion learning models. 2) Supporting factors for success include educators' understanding of humanistic theory, active students, and adequate facilities and infrastructure. 3) Inhibiting factors include limited space for educators to interact with students, resources, and teacher training that still need to be considered for optimal learning.